Virtual radar ice buoys – a method for measuring fine-scale sea ice drift - J. Karvonen (The Cryosphere, 2016)
Here we present an algorithm for continuous ice drift estimation based on coastal and ship radar data. The ice drift is estimated for automatically selected ice targets in the images. These targets are here called virtual buoys (VBs) and are tracked based on an optical flow method. To maintain continuous ice drift tracking new VBs are added after a given number of VBs have been lost; i.e. they can not be tracked reliably any more. Here we also apply the algorithm to data of three test cases to demonstrate its capabilities and properties. Two of these cases use coastal radar data and one ship radar data. Ice drift velocity and direction information derived from the VB motion are computed and compared to the prevailing ice and weather conditions. Also a quantity measuring the local divergence or convergence is computed for some VBs to demonstrate the capability to estimate derived kinematic sea ice parameters from VB location time series. The results produced by the algorithm can be used as an input for estimation of the dynamic properties of sea the ice field, such as ice divergence or convergence, shear, vorticity, and total deformation.